RANK signals from CD4(+)3(−) inducer cells regulate development of Aire-expressing epithelial cells in the thymic medulla - Rossi, Simona W. (The Rockefeller University Press, 2007)
Aire-expressing medullary thymic epithelial cells (mTECs) play a key role in preventing autoimmunity by expressing tissue-restricted antigens to help purge the emerging T cell receptor repertoire of self-reactive specificities. Here we demonstrate a novel role for a CD4(+)3(−) inducer cell population, previously linked to development of organized secondary lymphoid structures and maintenance of T cell memory in the functional regulation of Aire-mediated promiscuous gene expression in the thymus. CD4(+)3(−) cells are closely associated with mTECs in adult thymus, and in fetal thymus their appearance is temporally linked with the appearance of Aire(+) mTECs. We show that RANKL signals from this cell promote the maturation of RANK-expressing CD80(−)Aire(−) mTEC progenitors into CD80(+)Aire(+) mTECs, and that transplantation of RANK-deficient thymic stroma into immunodeficient hosts induces autoimmunity. Collectively, our data reveal cellular and molecular mechanisms leading to the generation of Aire(+) mTECs and highlight a previously unrecognized role for CD4(+)3(−)RANKL(+) inducer cells in intrathymic self-tolerance.